2022
DOI: 10.1515/med-2022-0458
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 fear, post-traumatic stress, growth, and the role of resilience

Abstract: Understanding the factors through which pandemic fear may be associated not just with distress, but also with growth outcomes is crucial to informing interventions across population groups and cultural settings. To achieve this aim, in a cross-sectional study, we examined the relationship between the fear of COVID-19, post-traumatic stress and post-traumatic growth while assessing the moderating role of trait resilience. Findings showed that fear of COVID-19 was associated with both stress and growth outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The present study found a positive association between fear of COVID-19 and PTG, which is consistent with the findings of period studies on PTG (Fino et al, 2022a, 2022b). Most critically, this study showed a positive U-curve relationship between PTG and experiencing distress, that is, high levels of fear of COVID-19 are most associated with the greatest levels of growth.…”
Section: Discussionsupporting
confidence: 92%
“…The present study found a positive association between fear of COVID-19 and PTG, which is consistent with the findings of period studies on PTG (Fino et al, 2022a, 2022b). Most critically, this study showed a positive U-curve relationship between PTG and experiencing distress, that is, high levels of fear of COVID-19 are most associated with the greatest levels of growth.…”
Section: Discussionsupporting
confidence: 92%
“…20 An employee's personal resources, such as resilience levels, may be a positive mechanism that helps employees combat stress and anxiety. 40 Mental resilience can buffer against the adverse effects of post-traumatic stress 41 and fear of COVID-19 on mental health. 40 However, the concept of psychological resilience has been widely studied as a clinical treatment while rarely been applied to the investigation into public mental In summary, the purpose of this study is threefold: firstly, it aims to investigate whether there's positive significant correlation between fear of COVID-19 and psychological distress among tour guides (Hypothesis 1).…”
Section: The Moderating Role Of Psychological Resiliencementioning
confidence: 99%
“…An umbrella review reported that the prevalence of PTSD was high (13.52%) among frontline healthcare workers during the COVID-19 pandemic (5). Resilience acts as a buffer against PTSD (6,7) and is usually defined as the successful adaptation to adversity, trauma, tragedy, threats, or significant sources of stress (8). Building resilience can help healthcare workers to better cope with and recover from adverse events to achieve better wellbeing (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%